(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Photochromic blockers of voltage gated ion channels are powerful tools for the control of neuronal systems with high spatial and temporal precision. We now introduce fotocaine, a new type of photochromic channel blocker based on the long-lasting anesthetic fomocaine. Fotocaine is readily taken up by neurons in brain slices and enables the optical control of action potential firing by switching between 350 and 450 nm light. It also provides an instructive example for “azologization”, that is, the systematic conversion of an established drug into a photoswitchable one.